Endothelial Domes Encapsulate Adherent Neutrophils and Minimize Increases in Vascular Permeability in Paracellular and Transcellular Emigration - Phillipson, Mia (Public Library of Science, 2008)
Local edema, a cardinal sign of inflammation associates closely with neutrophil emigration. Neutrophil emigration has been described to occur primarily through endothelial junctions (paracellular) and more rarely directly through endothelial cells (transcellular). Recently, we reported that unlike in wild-type (wt) mice, Mac-1-/- (CD11b) neutrophils predominantly emigrated transcellularly and was significantly delayed taking 20–30 min longer than the paracellular emigration (wt). In the present study we noted significant anatomical disruption of the endothelium and hypothesized that transcellular emigration would greatly increase vascular permeability. Surprisingly, despite profound disruption of the endothelial barrier as the neutrophils moved through the cells, the changes in vascular permeability during transcellular emigration (Mac-1-/-) were not increased more than in wt mice. Instead increased vascular permeability completely tracked the number of emigrated cells and as such, permeability changes were delayed in Mac-1-/- mice. However, by 60 min neutrophils from both sets of mice were emigrating in large numbers. Electron-microscopy and spinning disk multichannel fluorescence confocal microscopy revealed endothelial docking structures that progressed to dome-like structures completely covering wt and Mac-1-/- neutrophils. These domes completely enveloped the emigrating neutrophils in both wt and Mac-1-/- mice making the mode of emigration underneath these structures extraneous to barrier function. In conclusion, predominantly paracellular versus predominantly transcellular emigration does not affect vascular barrier integrity as endothelial dome-like structures retain barrier function.